Mechanical, thermo‐mechanical, thermal, and swelling properties of EPDM‐organically modified mesoporous silica nanocomposites. (17th November 2015) - Acharya, Himadri; Srivastava, Suneel K.
Abstract : Ethylene‐propylene‐diene terpolymer nanocomposites has been developed using organically modified mesoporous silica nanoparticles by solution blending method. Hydrophilic mesoporous silica nanoparticles (MCM‐41) of ∼100 nm in sizes were synthesized via a template‐directed method, functionalized with trimethylchlorosilane (TMS) to produce hydrophobic silica (OS). The X‐ray diffraction (XRD), transmission electron microscopy (TEM) and scanning electron microscopy (SEM) analysis suggest that OS are homogeneously dispersed in the EPDM matrix and can maintain its pore structure effectively in the nanocomposites. The EPDM/OS nanocomposite exhibits a significant improvement in mechanical and thermal properties with respect to neat EPDM. A significant increase in tensile strength (TS) approximately 200% was observed at very low wt% of organosilica content in the nanocomposite. Dynamic mechanical analysis also exhibits the improvement in storage modulus for nanocomposites. Thermogravimetric analysis shows a thermal stability enhancement by approximately 25°C of EPDM nanocomposites containing 3 wt% OS when 25% weight loss was selected as point of comparison. The solvent uptakes in nanocomposites were comparable with the porous sites and free volume in EPDM matrix on OS incorporation. POLYM. COMPOS., 38:E371–E380, 2017. © 2015 Society of Plastics Engineers